The Arms-Bearing Woman and British Theatre in the Age of Revolution, 1789-1815 - Burdett, Sarah (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book explores shifting representations and receptions of the arms-bearing woman on the British stage during a period in which she comes to stand in Britain as a striking symbol of revolutionary chaos. The book makes a case for viewing the British Romantic theatre as an arena in which the significance of the armed woman is constantly remodelled and reappropriated to fulfil diverse ideological functions. Used to challenge as well as to enforce established notions of sex and gender difference, she is fashioned also as an allegorical tool, serving both to condemn and to champion political and social rebellion at home and abroad. Magnifying heroines who appear on stage wielding pistols, brandishing daggers, thrusting swords, and even firing explosives, the study spotlights the intricate and often surprising ways in which the stage amazon interacts with Anglo-French, Anglo-Irish, Anglo-German, and Anglo-Spanish debates at varying moments across the French revolutionary and Napoleonic campaigns. At the same time, it foregrounds the extent to which new dramatic genres imported from Europe -notably, the German Sturm und Drang and the French-derived melodrama- facilitate possibilities at the turn of the nineteenth century for a refashioned female warrior, whose degree of agency, destructiveness, and heroism surpasses that of her tragic and sentimental predecessors. Dr Sarah Burdett is Lecturer in English Literature at University College London, UK. She received her BA in English from the University of East Anglia and completed her MA and PhD at the Centre for Eighteenth Century Studies, University of York. Sarah has published work on female violence, practice-led theatre research, eighteenth-century Irish drama, and the Georgian actress, and has been awarded Research Fellowships from the Bodleian Library, Oxford; and the Folger Shakespeare Library, Washington DC.
1. Introduction: The Armed Woman Enters -- 2. Unbrutifying Man': Armed Women and Male Reform in Elizabeth Inchbald's Dramas -- 3. 'The Ruthless Queen': Lady Macbeth and Margaret of Anjou on the Post-Reign of Terror London Stage -- 4. 'The Merit of her Patriotism': Charlotte Corday in British Drama, 1794-1804 -- 5. 'I Drew my Knife and in his Bosom Stuck it': Armed Heroines and Anglo-German Drama -- 6. 'Yet are Spain's Maids No Race of Amazons': Spain's Female Warriors in Anglo-European Drama -- 7. Epilogue: The Armed Woman Exits.
Keywords: Drama; Literature, Modern -- 18th century; Literature, Modern -- 19th century; Sex; Drama; Eighteenth-Century Literature; Nineteenth-Century Literature; Gender Studies